Communication Pattern of Da'wah Minhajus Sunnah Foundation in Forming Militancy of Salafiyah Community in Medan City - Sufrida Said; Rubino Rubino; Efi Brata Madya (UNIVERSITAS PAKUAN, 2023)
Communication network refers to research techniques used to identify the structure of communication within a system or community. It involves analyzing relationship data regarding communication flows using different types of interpersonal relationships as units of analysis. Groups with participatory growth processes will achieve higher cohesiveness thresholds. This study aims to analyze how the communication network, what are the steps, and what are the supporting and inhibiting factors of the leadership of Islamic boarding schools in increasing the social cohesiveness of the Acehnese ethnic community in the ma`had fahmussalam al-aziziyah environment. The methodology used in this research is descriptive qualitative method. Data collection techniques were carried out by interviews, observation and documentation. Based on the results of observations and interviews, the researchers found that the steps taken by the leaders of Islamic boarding schools in increasing the social cohesiveness of the Acehnese ethnic community in the ma`had fahmussalam al-aziziyah environment were as follows. Collectives can be formed when each member of the group has the same interests. The communication network consists of individuals who are connected to each other through a continuous communication gimmick method. Steps in Improving the Social Cohesiveness of the Acehnese People in the Ma`had Fahmussalam al-Aziziyah Environment In terms of increasing cohesiveness in a group or community, there must be methods or steps that must be taken to increase cohesiveness within a group